Racial Disparities in the Adherence to an Enhanced Recovery after Cesarean Protocol (ERAC): A Retrospective Observational Study at Two NYC Hospitals, 2016–2020 - Gilman, Abbey T.; Kim, Jessica; Jiang, Silis Y.; Abramovitz, Sharon E.; White, Robert S. (American Journal of Perinatology, 2025)
Enhanced recovery after surgery programs for cesarean deliveries (ERAC) aim to optimize the quality of care for all patients. Race is not routinely monitored in ERAC programs. Given the extensive reports of racial disparities in obstetrical care, the goal of this study was to investigate racial differences in adherence rates to individual ERAC protocol elements.A cohort study was performed among cesarean delivery patients enrolled in an ERAC program at two hospitals from October 2016 to September 2020. Compliance with anesthesia-specific ERAC metrics, including ketorolac, ondansetron, and active warming methods, were compared by race. Race was self-reported by all patients. Logistic regression models stratified by pre- and post-ERAC status were used to assess relationships.The sample consisted of 7,812 cesarean delivery patients, of which 4,640 were pre-ERAC (59.4%) and 3,172 were post-ERAC (40.6%). There were no racial differences found in overall ERAC protocol adherence, active warming methods, or ondansetron administration in the pre- and post-ERAC groups. The odds of ketorolac administration in Black patients (adjusted odds ratio [aOR]: 0.72; 95% confidence interval [CI]: 0.55–0.95; p = 0.020) and Asian patients (aOR: 0.81; 95% CI: 0.68–0.98; p = 0.027) pre-ERAC were significantly lower compared with white patients. In the post-ERAC group, this disparity persisted in Black (aOR: 0.80; 95% CI: 0.65–0.99; p = 0.042) and Asian patients (aOR: 0.85; 95% CI: 0.73–0.98; p = 0.023).Appropriate implementation and adherence to all elements of the ERAC program may provide a practical approach to reducing disparities in outcomes and ensuring equitable treatment for all patients.
Keywords: cesarean delivery; ERAS; health care disparities; maternal health; obstetric; social determinants of health